Avaliação reológica do período de consolidação de argamassas colantes - Modler, Luís Eduardo Azevedo (2017)
This work has presented an analysis of the consolidation process of dry set mortars, using the oscillatory rheometry technique as a method of approach. The method was applied to a set of mortar mixtures, whose proportions between its components were varied within limits stipulated by the author by means of an experimental planning, following the Central Composite Rotational Design (CCRD) methodology, in which the proportions between the dry set mortars components represented the independent factors. The samples were subjected to a shear strain controlled by the device, while both the resulting shear stress ( ) and the phase angle ( ) were measured. The strain was applied to the sample in a 1Hz frequency, resulting in one extraction per minute over 200 minutes. In the proposed approach the compactness properties of mixtures were evaluated as dependent factors, from the Wet Packing Method (WPM), as also were the fundamental rheological properties, interpreted from the oscillatory rheometry, and their derived factors, calculated from the former ones. This work aimed to comprehend the consolidation process as an inherent phenomenon of dry set mortar, as well as to relate their kinetics to the parameters assumed as independent factors. The analyzing methodology involved qualitative and quantitative evaluations of the rheological quantities over the performed tests, in addition to a statistical analysis which related the and values to the independent factors. The results showed that the consolidation process of dry set mortars is a continuous phenomenon that occurs at least since the first 30 minutes after the mixture. It was also evidenced that the chosen fundamental rheological properties can describe the phenomenon from their measurement via oscillatory rheometry. The independent factors presented, at different levels, influence on the observed consolidation phenomenon. It was observed that the contents of moisture and sand tend to delay the process as a whole and that the polymers contents used (EVA and HEC) have the opposite effect. It was possible to notice a relationship between the granular mixtures compactness and the consolidation process, as the mixtures with compacter granular structure tend to delay the consolidation process more than mixtures with lower compactness levels, due to their bigger content of excess water.